2016
DOI: 10.4049/jimmunol.1500679
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Virulence Factor SsrAB Regulated Factor Modulates Inflammatory Responses by Enhancing the Activation of NF-κB Signaling Pathway

Abstract: Effector proteins encoded by Salmonella pathogenicity islands play a key role in promoting bacterial intracellular survival, colonization, and pathogenesis. In this study, we investigated the function of the virulence-associated effector SrfA (SsrAB regulated factor) both in macrophages in vitro and in infected mice in vivo. SrfA was secreted into the cytoplasm during S. Typhimurium infection and disassociated IL-1R–associated kinase-1 (IRAK-1) from the IRAK-1–Toll interacting protein (Tollip) complex by inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Therefore, one or multiple genes from SPI-2 are involved in PD-L1 induction of IECs. To further identify a single bacterial component important in PD-L1 induction, seven SPI-2encoded effector mutants were created and tested (⌬spvC, ⌬sspH1, ⌬slrp, ⌬sseJ, ⌬sseL, ⌬spvD, and ⌬srfA; see Table S2 in the supplemental material) based on their suggested effector functions (20,21,30). Each strain was inoculated at four doses (1 ϫ 10 7 , 3 ϫ 10 7 , 5 ϫ 10 7 , and 8 ϫ 10 7 CFU/well) to generate respective intracellular bacteria versus PD-L1 expression curves (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, one or multiple genes from SPI-2 are involved in PD-L1 induction of IECs. To further identify a single bacterial component important in PD-L1 induction, seven SPI-2encoded effector mutants were created and tested (⌬spvC, ⌬sspH1, ⌬slrp, ⌬sseJ, ⌬sseL, ⌬spvD, and ⌬srfA; see Table S2 in the supplemental material) based on their suggested effector functions (20,21,30). Each strain was inoculated at four doses (1 ϫ 10 7 , 3 ϫ 10 7 , 5 ϫ 10 7 , and 8 ϫ 10 7 CFU/well) to generate respective intracellular bacteria versus PD-L1 expression curves (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Typhi and downregulated in S . Typhimurium include lpxR (t1208/STM14_1612), a lipid A-modifying protein that modulates the ability of lipid A to stimulate Toll-like receptor 4 (TLR4) ( 32 ) and promotes Salmonella growth inside macrophages ( 33 ), and srfA and srfB , virulence factors expressed under SPI-1-inducing conditions ( 34 ) and reported to modulate inflammatory signaling ( 35 ). Additionally, several hypothetical proteins, t0944 (STM14_2352), t1774 (STM14_1312), and t2782 (STM14_3479), were upregulated in S .…”
Section: Resultsmentioning
confidence: 99%
“…Genome analysis suggested that the srfABC cluster was located in the horizontally acquired island adjacent to a putative lipoprotein transport system that is responsible for its secretion (Nykyri et al ., ). Among the proteins coded for by the cluster, SrfA was expected to be secreted to effect nuclear transcription (Worley et al ., ) and was determined to be a secreted virulence effector of Salmonella that modulates host inflammatory responses by promoting the activation of nuclear factor‐kappa B (NF‐κB) signalling pathways (Lei et al ., ). This is in contrast to the results for P. cichorii in the present study; this difference in SrfA function between mammalian and plant pathogens requires further study.…”
Section: Discussionmentioning
confidence: 97%